The Antibacterial Applications of Graphene and Its Derivatives. Issue 31 (7th July 2016) - Shi, Lin; Chen, Jiongrun; Teng, Lijing; Wang, Lin; Zhu, Guanglin; Liu, Sa; Luo, Zhengtang; Shi, Xuetao; Wang, Yingjun; Ren, Li
Abstract : Graphene materials have unique structures and outstanding thermal, optical, mechanical and electronic properties. In the last decade, these materials have attracted substantial interest in the field of nanomaterials, with applications ranging from biosensors to biomedicine. Among these applications, great advances have been made in the field of antibacterial agents. Here, recent advancements in the use of graphene and its derivatives as antibacterial agents are reviewed. Graphene is used in three forms: the pristine form; mixed with other antibacterial agents, such as Ag and chitosan; or with a base material, such as poly (N‐vinylcarbazole) (PVK) and poly (lactic acid) (PLA). The main mechanisms proposed to explain the antibacterial behaviors of graphene and its derivatives are the membrane stress hypothesis, the oxidative stress hypothesis, the entrapment hypothesis, the electron transfer hypothesis and the photothermal hypothesis. This review describes contributions to improving these promising materials for antibacterial applications. Abstract : Recent advancements in using graphene derivatives as antibacterial agents are reviewed. The mechanisms put forward to explain their antibacterial behaviors are various, mainly including membrane stress, oxidative stress, photothermal, entrapment isolation and electron transfer hypothesis. The goal of this review is to contribute to the improvement of the functionality of these promising materials in antibacterial applications.